(untitled) (مجلة الفاروق للعلوم, 2026)
Recently, artificial intelligence started to invade medicine in its entire fields: diagnosis and therapy. Artificial intelligence can be a key part in the diagnostic medicine field for easy, fast, and accurate diagnosis of diseases. Thus, machine learning systems or so called intelligent systems that takes on the unpracticed physicians’ job are in urgent need. In this paper, we present the use of two different intelligent systems for the skin tumor classification system. The approach is based on both image processing techniques and artificial intelligence tools such as backpropagation and Radial basis function neural networks. The main aim of this study is to investigate the best performance and accuracy in such medical classification application between the both used networks. Moreover, in this work we propose a simple image processing algorithm for segmenting the skin tumor from images using simple and fast techniques such as Gaussian filtering and image opening. Upon processing and rescaling the images are fed to both networks to be trained and tested and accuracy, training time, and error were calculated. Experimentally, both networks succeeded in generalizing the correct classification results of the unseen skin tumor images but with different rates, accuracies, and errors. As a result, it was found that a radial basis function network outperforms the backpropagation network in terms of accuracy, training time, and minimum square error achieved.